2014
DOI: 10.22146/jsv.5420
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thawing Temperature on Sperm Quality of Friesian Holstein Bulls

Abstract: The percentage of sperm motility and morphology are important criteria in evaluating the quality of sperm before it is used for artificial insemination (AI). This study was conducted to observe post thawing motility and abnormal morphology of spermatozoa Friesian Holstein (FH). The materials were used 10 straws of FH bulls in the form of 0.25 ml. A total of 10 straws then divided into two treatment groups of  thawing  in water at 37°C and water 8°C, respectively. An examination of the motility and morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Yendraliza et al (2019) showed abnormalities of frozen semen of Bali cattle in Andromed ® diluent, with various percentages of carrot juice after thawing, to be around 5.17% to 10.50%. Utami and Tophianong (2014) showed that the highest abnormality of sperm thawed in water at 8 o C and 37 o C was 20% and 23%. Abnormal data in previous studies using frozen semen of non-sexed Limousine cattle was 6.93 ± 1.37% (Mahfud et al 2019).…”
Section: Intact Plasma Membrane (Ipm) Simmental Frozenmentioning
confidence: 99%
“…Yendraliza et al (2019) showed abnormalities of frozen semen of Bali cattle in Andromed ® diluent, with various percentages of carrot juice after thawing, to be around 5.17% to 10.50%. Utami and Tophianong (2014) showed that the highest abnormality of sperm thawed in water at 8 o C and 37 o C was 20% and 23%. Abnormal data in previous studies using frozen semen of non-sexed Limousine cattle was 6.93 ± 1.37% (Mahfud et al 2019).…”
Section: Intact Plasma Membrane (Ipm) Simmental Frozenmentioning
confidence: 99%
“…Normal spermatozoa motility ranges from 70-90% with fast movement [29]. Spermatozoa move because of the role of the spermatozoa tail, due to the tail of the spermatozoa containing many mitochondria that act as energy producers in the form of ATP so that spermatozoa move forward [30]. Sperm motility of ejaculate had been affected by the temperature at the time of storage and during examination.…”
Section: Issn 2087-2852 E-issn 2338-1655mentioning
confidence: 99%
“…It can be concluded that this semen deserves to be processed further. Likewise, Utami et al (2014) stated that spermatozoa abnormalities were no more than 12% to 23% and the normal percentage was between 77% to 88% in livestock. However, the result of this study was lower than that of Rahmiati et al (2018) with an average abnormality of 10.34% in Aceh cattle and higher than that of Kaiin and Kaiin and Gunawan (2015) with abnormalities of 1.47% in Simmental bull previously reared at RAIC Pucak.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%